Sifat Kegenjahan dan Toleran Kekeringan Beberapa Galur Padi sebagai Calon tetua - Yuniati P. Munarso (Universitas Trunojoyo Madura, 2010)
An experiment to evaluate the dwarfness and the drought tolerance of 97 rice varieties/lines, collected from various source institutes surround West Java has been executed at Muara Research Station, Bogor in 2009. Any varieties/lines could be stated as drwarf when it has harvest time of 90 – 104 days. Meanwhile, it could be stated as drought tolerance when the line was scored 1 (tip of the leaves dryied) and has growth recovery respons of more than 90%. The dwarfness test showed that the tested varieties/lines had a varied 50% flowering time, ranging from 58-104 days after seeding (DAS). Amount of 29 out of 97 lines/varieties could be classified as very dwarf lines/varieties, with 50% flowering time of 67-79 DAS. This means that those lines/varieties could be harvested at the age of 92-104 DAS. However, those lines/varieties were also identified to have various performance score, i.e. ranging from 1-7. Several lines/varieties with good dwarf ness characteristic are OM AS996 (76 DAS; PAcp 1), OM CS2000 (73 DAS, PAcp 3), MUDGO (67 DAS;PAcp 7), dan OM 1490 (76 DAS, PAcp 3). Two lines/varieties (OM 1490 and B11742-RS*2-3-MR-34-1-1-3) was identified to be the most drought tolerance lines. Meanwhile, 11 lines/varieties were graded as tolerance to drought lines, with ability of growth recovery 90%. They were Sensari, Goarsail, OM 4498, OM 2395, B11742-RS*2-3-MR-34-1-1-4, S4616, OM 2514, Meraoke, Mira-1, Bestari, and B11742-RS*2-3-MR-34-1-4-3. Based on those tests, it was found that rice lines of OM 1490, OM 4498, OM 2395, B11742-RS*2-3-MR-34-1-1-3, B11742-RS*2-3-MR-34-1-1-4, and B11742-RS*2-3-MR-34-1-4-3 were the most suitable parental lines in the development of such rice varieties.